Additive manufacturing of magnetic materials. (October 2020) - Chaudhary, V.; Mantri, S.A.; Ramanujan, R.V.; Banerjee, R.
Abstract: Additive manufacturing (AM) is an attractive process to manufacture net shape, complex, engineering components with minimum waste; however, it has been largely applied to structural materials. AM of functional materials, such as magnetic materials, has received much less attention. Magnetic materials are of high and growing interest in an extremely wide range of applications, e.g., electronic devices, rotating electrical machines, electric vehicles, wind turbines, magnetic cooling, electromagnetic shielding microphones, mobiles, laptops, etc. The processing of functional materials by AM can result in novel magnetic components with improved performance and lower processing cost, motivating the present review on AM of magnetic materials. We review commonly used AM techniques, their working principles, and applications to magnetic materials. We discuss the use of the laser engineering net shaping (LENS) process to produce soft and hard magnets. This technique can also be readily employed to process compositionally graded structures for accelerated materials development through combinatorial/high throughput investigations. Such graded structures can exhibit a wide range of functional and structural properties. The structural and magnetic properties of AM processed Fe-Si, Ni-Fe, Fe-Co, soft magnetic composites, soft magnetic oxides, magnetic shape memory alloys, magnetocaloric alloys as well as high entropy alloys are described. AM of hard magnetic materials, including Alnico, Sm-Co, Nd-Fe-B and Ce-Co alloys is elucidated. The current and future trends in this area are outlined.